Cardiac and neurological abnormalities in v-fps transgenic mice. - Yee, S P (1989)
Transgenic mice that widely express the v-fps protein-tyrosine kinase develop several independent pathological conditions, in addition to a high tumor incidence. v-fps expression and protein-tyrosine kinase activity in the heart were directly correlated with cardiac enlargement. This cardiomegaly was accompanied by severe myocardial and endocardial damage, which was concentrated in the left ventricular wall, and characterized by a progressive atrophy and necrosis of cardiac muscle fibers with concomitant fibrosis. This pathology was associated with congestive heart failure. Mice from five lines developed a marked trembling, correlated with expression of the v-fps transgene in the brain, and two lines showed a striking bilateral enlargement of the trigeminal nerves. Unlike tumor formation, these cardiac and neurological phenotypes were evident shortly after birth and showed 100% penetrance. The pleiotropic effects of the v-fps transgene suggest the involvement of protein-tyrosine kinases in mammalian neural development and cardiac function.